Effects of High-Intensity Exercise Training on Adipose Tissue Mass, Glucose Uptake and Protein Content in Pre- and Post-menopausal Women - Mandrup, Camilla M.; Roland, Caroline B.; Egelund, Jon; Nyberg, Michael; Enevoldsen, Lotte Hahn; Kjaer, Andreas; Clemmensen, Andreas; Christensen, Anders Nymark; Suetta, Charlotte; Frikke-Schmidt, Ruth; Utoft, Betina Bernhard; Kristensen, Jonas Møller; et al. (Frontiers in Sports and Active Living, 2020)
The menopausal transition is accompanied by changes in adipose tissue storage, leading to an android body composition in postmenopausal women, which is associated with increased risk of type 2 diabetes and cardiovascular disease. Estrogen probably affects adipose tissue depots differently, depending on location, but it is not clear, how menopausal status influences adipose tissue insulin sensitivity, protein content regarding lipogenesis/lipolysis and mitochondrial function or the impact of exercise training to reduce adipose tissue depots. Healthy, normal-weight pre- (n=21) and postmenopausal (n=20) women participated in high-intensity exercise training three times a week for 12 weeks. Adipose tissue distribution was determined by dual energy x-ray absorptiometry and magnetic resonance imaging. Adipose tissue glucose uptake was assessed by positron emission tomography/computed tomography (PET/CT) by the glucose analogue [18F]fluorodeoxyglucose ([18F]FDG) during continuous insulin infusion (40mU·m-2·min-1). Protein content regarding insulin signaling, lipogenesis/lipolysis and mitochondrial function in abdominal and femoral white adipose tissue biopsies were determined by Western blot. The mean age difference between the pre- and the postmenopausal group were 4.5 years. Exercise training reduced subcutaneous ( 4%) and visceral ( 6%) adipose tissue masses similarly in pre- and postmenopausal women. Insulin-stimulated glucose uptake, assessed by [18F]FDG-uptake during PET/CT, in abdominal, gluteal, and femoral adipose tissue depots were similar in pre- and postmenopausal women, despite skeletal muscle insulin resistance in post- compared to premenopausal women in the same cohort. Insulin-stimulated glucose uptake in adipose tissue depots was not changed after three months of high-intensity exercise training, but insulin sensitivity was higher in visceral compared to subcutaneous adipose tissue depots ( 139%). However, postmenopausal women exhibited increased hexokinase and adipose triglyceride lipase content in subcutaneous abdominal AT. Physical activity in the early postmenopausal years can contribute to reduced abdominal obesity, but insulin sensitivity of adipose tissue is unchanged.